Makelar dalam Transaksi Ekonomi (Analisis Fatwa DSN MUI No. 151/DSN-MUI/VI/2022 Tentang Akad Samsarah) - Ahmad Hamdi; Abd. Rahman; Nahe'i Nahe'i (Iltizam : Jurnal Ekonomi dan Keuangan Islam, 2024)
Brokers in economic transactions are common jobs undertaken by society. However, in practice, brokers often pose problems, especially for consumers or buyers. It is not uncommon for buyers to find that the price set during the transaction is not the price set by the owner of the goods, but rather a price added by the broker. The significant price difference from the original price becomes a separate problem for the community. This article aims to explain the practice of brokers in Islam by analyzing the Fatwa DSN MUI NO. 151/DSN-MUI/VI/2022 on Samsarah Contracts. The focus of this article is: What is the nature of brokers in Islam? How does the Fatwa DSN MUI No. 151/DSN-MUI/VI/2022 on Samsarah Contracts play a role in ensuring the legality of broker practices in Indonesia? In this article, researchers use a research library approach. Primary data sources include literature on brokers in Islam. In Islam, brokerage is considered an allowed practice; a broker aims to provide assistance to both the buyer and the owner of the goods to be sold. Meanwhile, the role of Fatwa DSN MUI NO. 151/DSN-MUI/VI/2022 has outlined the technical implementation of broker services and provided arguments in accordance with Islamic Sharia teachings.